Majas Metafora dalam Anime Fune o Amu Karya Shion Miura - Putri, Yolanda Ardiana; Yani, Damai (Lembaga Yasin AlSys, 2025)
Metaphor is a figure of speech that implicitly compares two things, whether physical objects, ideas, characteristics, or actions without using direct comparative words. According to Nurgiyantoro, a metaphor is an implied form of analogy, while the Kamus Besar Bahasa Indonesia defines it as the use of a word or group of words in a non-literal sense, serving as a comparative expression based on meaning similarity. This study aims to describe the types and meanings of metaphors in the anime Fune O Amu by Shion Miura. The research employs a descriptive qualitative approach using Stephen Ullmann’s theory of metaphor as the analytical framework. The findings reveal 20 instances of metaphorical expressions in the anime, consisting of 1 anthropomorphic metaphor, 2 animal metaphors, 10 abstraction metaphors, and 7 synesthetic metaphors. These findings indicate that metaphorical language in Fune O Amu is used in varied ways to enhance expressive meaning and emotion, as well as to deepen the aesthetic experience in this visual literary work. The study concludes that anime, as a form of modern literature, utilizes metaphor not merely as a rhetorical device but as a powerful tool for generating deep and imaginative meaning.